Kafedra sportivnych sooruzenij i industrii CPbGUFKa im. P. F.Lesgafta - Zestjannikov, L. V.; Eremin, I. B. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
Faculty of sports constructions and the industries of the Saint Petersburg state P.F. Lesshaft's university of physical culture has been created in 2002 as the only thing in Russia the educational-scientific division engaged in ques-tions of sports constructions. The faculty actively participates in definition of strategy of development of a network of sports constructions in the Russian Federation, develops and realizes together with bodies of the government of the program of development of an infrastructure in area of physical culture and sports.